2018
DOI: 10.1111/sji.12714
|View full text |Cite
|
Sign up to set email alerts
|

Impaired neutrophil extracellular traps and inflammatory responses in the peritoneal fluid of patients with liver cirrhosis

Abstract: Liver cirrhosis (LC) is an inflammatory process associated with impaired functions in adaptive and innate immune responses at both systemic and local levels, also referred as Cirrhosis-Associated Immune Dysfunction. In this study, we evaluated the functionality of neutrophils from ascitic fluid (AF) of patients with hepatic cirrhosis by testing their ability to generate neutrophil extracellular traps (NETs) in vitro. To further determine the activation state of neutrophils, expression of the activation markers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 29 publications
0
15
1
Order By: Relevance
“…Our results agree with previous publications such as Blasi et al 29 who have showed that markers of NET are elevated in patients with cirrhosis as compared to healthy controls. However, in contrast to our findings, Agraz-Cibrián et al showed that neutrophils from ascites fluid from cirrhotic patients with spontaneous bacterial peritonitis had reduced ability to form NETs 30 . The same author also showed that neutrophils from peripheral blood of cirrhosis patients also had reduced ability of NET formation upon stimulation in vitro 31 .…”
Section: Discussioncontrasting
confidence: 99%
“…Our results agree with previous publications such as Blasi et al 29 who have showed that markers of NET are elevated in patients with cirrhosis as compared to healthy controls. However, in contrast to our findings, Agraz-Cibrián et al showed that neutrophils from ascites fluid from cirrhotic patients with spontaneous bacterial peritonitis had reduced ability to form NETs 30 . The same author also showed that neutrophils from peripheral blood of cirrhosis patients also had reduced ability of NET formation upon stimulation in vitro 31 .…”
Section: Discussioncontrasting
confidence: 99%
“…TAN-1 could be recognised as the ‘pro-tumour subpopulation’, which highly expressed pro-angiogenic factor VEGFA,36 pro-metastatic factor PLAU37 38 and LGALS3, a molecule with multiple functions beneficial for tumour progression, including enhancing proliferation and stemness of malignant cells, promoting angiogenesis, suppressing immune surveillance, promoting M2 macrophage differentiation and contributing to drug resistance39 40 (figure 2D (i)). TAN-2 consisted of an inflammatory subpopulation, which strongly expressed inflammation-associated genes NLRP3 and PDE4B,41 42 and neutrophil activation marker CD6943 44 (figure 2D (ii)). TAN-2 also strongly expressed pro-tumour molecules IL1RN and adrenomedullin (ADM) (figure 2D (ii)), which has been found to support tumour progression in other cancer types 45 46.…”
Section: Resultsmentioning
confidence: 99%
“…Once inflammation triggers endotoxins, cytokines, oxidative stress, and apoptosis, returning to baseline is much harder. [20][21][22] Most noteworthy, except for the SBP group, the mortality rate of patients with liver cirrhosis complicated with infection of any type decreased to 31.5%.…”
Section: Ta B L Ementioning
confidence: 97%